Analisis Faktor yang Mempengaruhi Tindakan Pencegahan Penularan HIV oleh ODHA Pada Orang lain - Nur Faisal; Rahmawati Azis; Muhammad Syafar (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; HIV is the main cause of the decline in the secondary immune system, which gradually leads to the AIDS stage. HIV and AIDS are pandemic, attacking millions of people in the world, men, women, and even children, so it is necessary to take steps to prevent HIV transmission. Aim; know the factors that influence the prevention of HIV transmission by PLWHA. Method; quantitative descriptive-analytic research with a cross-sectional design, with uvivariate, bivariate, and multivariate data analysis. Results; showed that the factors related to the prevention of HIV transmission by people living with HIV were a length of stay with HIV (p=0.000) and knowledge (p=0.000). In multiple logistic regression analysis, it was found that length of stay with HIV (p=0.007 95% CI: 0.014-0.517) and knowledge (p=0.014 95% CI: 1.343-14.451) were the most influencing factors to prevent HIV transmission. Conclusion; that the factors that most influence the prevention of HIV transmission by PLWHA are knowledge and duration of living with HIV.